Critical limit of copper in soil and plant for predicting response of oat (Avena sativa) in soils of Haryana - NARENDER; MALIK, R S; NARWAL, R P (The Indian Journal of Agricultural Sciences, 2014)
In order to evaluate critical level in oat (Avena sativa L.), laboratory and a screen house experiment was conducted at CCS HAU, Hisar. Bulk surface soil samples (0-15 cm) were collected from eighteen (18) different locations, in the state representing major soil groups of Haryana. The results of the study revealed that the relationship between Bray’s per cent yield against DTPA-Cu in soil and Cu concentration in plants indicated critical deficiency level of Cu in soil as 0.30 mg/kgand for oat plant it was 11.7 mg/kg which was statistically also at par.